Structural Elucidation of a Nonpeptidic Inhibitor Specific for the Human Immunoproteasome. (22nd February 2017) - Cui, Haissi; Baur, Regina; Le Chapelain, Camille; Dubiella, Christian; Heinemeyer, Wolfgang; Huber, Eva M.; Groll, Michael
Abstract: Selective inhibition of the immunoproteasome is a promising approach towards the development of immunomodulatory drugs. Recently, a class of substituted thiazole compounds that combine a nonpeptidic scaffold with the absence of an electrophile was reported in a patent. Here, we investigated the mode of action of the lead compound by using a sophisticated chimeric yeast model of the human immunoproteasome for structural studies. The inhibitor adopts a unique orientation perpendicular to the β5i substrate‐binding channel. Distinct interactions between the inhibitor and the subpockets of the human immunoproteasome account for its isotype selectivity. Abstract : Better off‐site : The binding mechanism of an industrially patented, non‐covalent, nonpeptidic, subunit‐specific immunoproteasome inhibitor was studied. This revealed distinct interactions that account for its isotype‐ and species‐selectivity towards the human immunoproteasome.